The Chemistry and the Anti-Inflammatory Activity of Polymethoxyflavonoids from Citrus Genus - Gianfranco Fontana; Maurizio Bruno; Francesco Sottile; Natale Badalamenti (MDPI AG, 2022)
Polymethoxyflavonoids (PMFs) are a large group of compounds belonging to the more general class of flavonoids that possess a flavan carbon framework decorated with a variable number of methoxy groups. Hydroxylated polymethoxyflavonoids (HPMFs), instead, are characterized by the presence of both hydroxyl and methoxy groups in their structural unities. Some of these compounds are the aglycone part in a glycoside structure in which the glycosidic linkage can involve the −OH at various positions. These compounds are particular to Citrus genus plants, especially in fruits, and they are present mainly in the peel. A considerable number of PMFs and HPMFs have shown promising biological activities and they are considered to be important nutraceuticals, responsible for some of the known beneficial effects on health associated with a regular consumption of Citrus fruits. Among their several actions on human health, it is notable that the relevant contribution in controlling the intracellular redox imbalance is associated with the inflammation processes. In this work, we aim to describe the status concerning the chemical identification and the anti-inflammatory activity of both PMFs and HPMFs. In particular, all of the chemical entities unambiguously identified by isolation and complete NMR analysis, and for which a biochemical evaluation on the pure compound was performed, are included in this paper.